Psychometric properties of the state-trait depression inventory (ST-DEP) in a adults of Lima - Sotelo L., Lidia (2012)
In this study the psychometric properties of State-Trait Depression Inventory (STDI) were analyzed in a sample of adults from metropolitan Lima, to obtain validity evidences that support its use both in the consulting and non-consulting population. Acceptable indicators of reliability were found through a method of internal consistency (Cronbach’s alpha), as well as content validity evidence, factorial validity and of criteria validity. Therefore, the STDI is a valid and reliable instrument to evaluate the affective component of depression.